KEPUASAN IBU BALITA TERHADAP PELAYANAN KADER DI POSYANDU MELATI DESA MAGEKAPA WILAYAH KERJA PUSKESMAS MAUKARO ENDE - Kopong, Pius Tokan; Sekunda, Maria S. (Kelimutu Nursing Journal, 2023)
Posyandu is a form of community participation in the health sector which is managed by cadres with the target of all members of the community. According to Siswanto (2010), one of the reasons for the lack of visits by toddlers to Posyandu is the lack of trust of mothers in the performance of Posyandu cadres. The aim of the study was to determine the level of satisfaction of mothers with toddlers regarding cadre services at Posyandu Melati, Magekapa Village, the working area of ​​the Maukaro Ende Health Center. The type of research used is descriptive with a survey research design. The population is all mothers under five who were recorded at the beginning of 2020, namely 42 people. The sampling technique is the total population by reason of the limited number of samples. The data collection tool is a questionnaire. The data were then analyzed and reported descriptively. The results showed that 23 people (54.76%) were dissatisfied with pre-activity services by cadres at Posyandu Melati, 27 people (64.29%) were dissatisfied with services during activities by cadres at Posyandu Melati and 25 people (59.52) %) were dissatisfied with post-activity services by cadres at Posyandu Melati. The results of the study concluded that the majority of respondents were dissatisfied with the services of cadres at Posyandu Melati, namely as many as 30 people (71.43%) and the rest were satisfied, namely as many as 12 people (28.57%). Therefore, the Puskesmas is advised to provide training to cadres so that cadres are able to provide optimal service and with a friendly approach to the community